2011
DOI: 10.1002/jrs.2857
|View full text |Cite
|
Sign up to set email alerts
|

Application of surface‐enhanced Raman scattering in cell analysis

Abstract: In surface-enhanced Raman scattering (SERS), the scattered intensity is drastically increased due to a resonant interaction with surface plasmons of coin metals. SERS is a nondestructive spectroscopic method applied also to biomedical samples. It inherits the advantages of normal Raman spectroscopy and at the same time overcomes the inherent low sensitivity problem. These properties endow SERS with exciting opportunities to be a successful analytical tool for cell analysis. SERS can be used to detect only mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 76 publications
(127 reference statements)
0
26
0
Order By: Relevance
“…The FaDu cells showed lower Raman intensities of nucleic acids, as indicated in the heights at 795, 1000, 1036, 1156, 1190, 1450, 1583, and 1603 cm -1 with compare to the FB cell SERS spectra, Besides the peaks mentioned above, the FaDu cells also showed lower peak heights in the 1603 cm -1 band, which corresponded to the C=C stretching mode of tyrosine and tryptophan [13]- [16]. The reduction in the Raman bands observed suggested that the amount of nucleic acid, protein and lipid could be lower in FaDu cells.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The FaDu cells showed lower Raman intensities of nucleic acids, as indicated in the heights at 795, 1000, 1036, 1156, 1190, 1450, 1583, and 1603 cm -1 with compare to the FB cell SERS spectra, Besides the peaks mentioned above, the FaDu cells also showed lower peak heights in the 1603 cm -1 band, which corresponded to the C=C stretching mode of tyrosine and tryptophan [13]- [16]. The reduction in the Raman bands observed suggested that the amount of nucleic acid, protein and lipid could be lower in FaDu cells.…”
mentioning
confidence: 87%
“…A pristine Au, control, and NN_1 were used as the detection reference for SERS measurement. The average spectra of FB and FaDu-cells have prominent spectral peaks at 617, 795, 1000, 1031-1036, 1154~1156, 1190~1196, 1326, 1449~1150, 1583, and 1602~1603 cm -1 [7], [13]- [16]. These spectral features arise from the molecular vibrations of cell components such as lipids, nucleic acids, and protein, as listed in Table 1.…”
Section: Biocompatibility and Raman Studies Of Fb And Fadu Cells On Fmentioning
confidence: 99%
“…It has been widely used in petrochemical engineering, [14] biomedicine, [15,16] geoarchaeology, [17] gem identification [18] and so on. Raman spectroscopy is extremely insensitive to polar materials like water and enjoys a bright application prospect in food quality control.…”
Section: Introductionmentioning
confidence: 99%
“…These vibrational transitions are dependent on the molecules; therefore, the inelastic scattering can be used to identify functional subgroups of the test molecule. 1 Devices capable of molecular detection are of great interest for many applications including cancer cell detection, [2][3][4] drug analysis, 5,6 and explosives detection. 7,8 Although extremely useful for bulk sample identification, conventional Raman spectroscopy has limited applications as the level of detection of the inelastic-scattered light is very low.…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of SERS lies with its ability to effectively "fingerprint" chemical species applicable to a wide variety of fields including material science, 12,13 biochemistry and biosensing, [2][3][4][5][6][14][15][16] and electrochemistry. 17,18 The dominant mechanism for most SERS processes is electromagnetic enhancement from the amplification of light by the excitation of localized surface plasmon resonances.…”
Section: Introductionmentioning
confidence: 99%